2021
DOI: 10.1016/j.medj.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Turning enemies into allies—reprogramming tumor-associated macrophages for cancer therapy

Abstract: Checkpoint blockade therapies that target inhibitory receptors on T cells have revolutionized clinical oncology. Antibodies targeting CTLA-4 or the PD-1/PD-1 ligand (PD-L1) axis are now successfully used alone or in combination with chemotherapy for numerous tumor types. Despite the clinical success of checkpoint blockade therapies, tumors exploit multiple mechanisms to escape or subvert the anti-tumor T cell response. Within the tumor microenvironment, tumor-associated macrophages (TAMs) can suppress T cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 134 publications
(174 reference statements)
0
20
0
Order By: Relevance
“…As detailed above, TREM2 is known to recognize a wide range of ligands, but it remains unknown which specific ligands it recognizes in the TME [48]. Nevertheless, these recent studies indicate that antagonistic anti-TREM2 mAbs have the potential to augment antitumor T cells responses, although the impact of blockade in the context of direct targeting mAb immunotherapy and ADCP warrants further investigation.…”
Section: Triggering-receptor-expressed On Myeloid Cells 2 (Trem2)mentioning
confidence: 99%
See 2 more Smart Citations
“…As detailed above, TREM2 is known to recognize a wide range of ligands, but it remains unknown which specific ligands it recognizes in the TME [48]. Nevertheless, these recent studies indicate that antagonistic anti-TREM2 mAbs have the potential to augment antitumor T cells responses, although the impact of blockade in the context of direct targeting mAb immunotherapy and ADCP warrants further investigation.…”
Section: Triggering-receptor-expressed On Myeloid Cells 2 (Trem2)mentioning
confidence: 99%
“…Concurrent work in murine tumor models by Molgora et al [ 191 ] demonstrated that treatment with anti-TREM2 mAb suppressed tumor growth, augmented antitumor effector T cell responses and reduced MRC1 + CX 3 CR1 + macrophages in the tumor infiltrate when combined with anti-PD-1 mAb therapy [ 191 ]. As detailed above, TREM2 is known to recognize a wide range of ligands, but it remains unknown which specific ligands it recognizes in the TME [ 48 ]. Nevertheless, these recent studies indicate that antagonistic anti-TREM2 mAbs have the potential to augment antitumor T cells responses, although the impact of blockade in the context of direct targeting mAb immunotherapy and ADCP warrants further investigation.…”
Section: Tam Repolarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, attention has been focused on TREM2-expressing tumor-associated macrophages (TAMs). TAMs represent a major component of the tumor microenvironment (TME), being primarily immunosuppressive and associated with poor prognosis [11][12][13]. TAMs can affect tumor growth, directly and indirectly, promoting tumor cell survival and proliferation, as well as angiogenesis, invasiveness, and immune evasion.…”
Section: Introductionmentioning
confidence: 99%
“…The presence and accumulation of pro-tumorigenic TIMs correlates with resistance to various cancer treatments (including immunotherapy) and poor patient outcomes (Sharma et al, 2017). Thus, reprogramming TIMs towards an anti-tumorigenic phenotype is an attractive strategy for cancer therapy that has shown efficacy across therapeutic modalities and tumor types in both preclinical and clinical studies (Kowal et al, 2019;Molgora and Colonna, 2021).…”
Section: Introductionmentioning
confidence: 99%